Avaliação do desempenho tático no Futsal em uma turma de atividade curricular desportiva - Celestini, João Vitor (Universidade Federal de São Carlos, 2017)
The objective of this research is to analyze an intervention in a Sports Curriculum Activity of futsal as well as the application process in test to evaluate the game performance. The research method consisted of strategic action research developed at a state school in São Carlos, for which the researcher carried out an intervention of ten classes that included the application of the TSAP test at the beginning and at the end of this process. The test itself is an effective evaluation method for team sports worked in a teaching unit because it is able to collect data that serves to understand the level of collective and individual game. The training was carried out from the tactical demands of the game based on the pedagogy of team sports. With the application of the intervention we can report that there was on the part of the students a concern with the objectives of the game and questions during the activities and the TSAP helped to see at the end of the intervention the performance of the students.
Evaluation of tactical performance in Futsal in a sport curricular activity class
Keywords: Atividade Curricular Desportiva; Team Sports Assessment Performance (TSAP); Esportes de invasão; Avaliação; Futsal; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL